Quantification of Anaplastic Lymphoma Kinase Protein Expression in Non–Small Cell Lung Cancer Tissues from Patients Treated with Crizotinib. (6th January 2020) - Hembrough, Todd; Liao, Wei-Li; Hartley, Christopher P; Ma, Patrick C; Velcheti, Vamsidhar; Lanigan, Christopher; Thyparambil, Sheeno; An, Eunkyung; Monga, Manish; Krizman, David; Burrows, Jon; Tafe, Laura J
Abstract: BACKGROUND: Crizotinib has antitumor activity in ALK (anaplastic lymphoma receptor tyrosine kinase)-rearranged non–small cell lung cancer (NSCLC). The current diagnostic test for ALK rearrangement is breakapart fluorescence in situ hybridization (FISH), but FISH has low throughput and is not always reflective of protein concentrations. The emergence of multiple clinically relevant biomarkers in NSCLC necessitates efficient testing of scarce tissue samples. We developed an anaplastic lymphoma kinase (ALK) protein assay that uses multiplexed selected reaction monitoring (SRM) to quantify absolute amounts of ALK in formalin-fixed paraffin-embedded (FFPE) tumor tissue. METHODS: After validation in formalin-fixed cell lines, the SRM assay was used to quantify concentrations of ALK in 18 FFPE NSCLC samples that had been tested for ALK by FISH and immunohistochemistry. Results were correlated with patient response to crizotinib. RESULTS: We detected ALK in 11 of 14 NSCLC samples with known ALK rearrangements by FISH. Absolute ALK concentrations correlated with clinical response in 5 of 8 patients treated with crizotinib. The SRM assay did not detect ALK in 3 FISH-positive patients who had not responded to crizotinib. In 1 of these cases, DNA sequencing revealed a point mutation that predicts a nonfunctional ALK fusion protein. The SRM assay did not detect ALK in any tumor tissue with a negative ALK status by FISH or immunohistochemistry. CONCLUSIONS: ALK concentrations measured by SRM correlate with crizotinib response in NSCLC patients. The ALK SRM proteomic assay, which may be multiplexed with other clinically relevant proteins, allows for rapid identification of patients potentially eligible for targeted therapies.